Strong configuration interactions in Be-like ions. (31st January 2017) - Li, X; Yang, Jiamin; Zhang, Jiyan; Zhao, Yang; Xiong, Gang; Hu, Zhimin; Yang, Guohong
Abstract: Strong configuration interactions are observed in Be-like ions between 1 s 1 2 s 2 nl 1 and 1 s 1 2 p 2 nl 1 . Such configuration interactions not only make a remarkable and systematic difference to the k-shell transition from 1 s 1 2 p 2 nl 1 to 1 s 2 2 p 1 nl 1, but they also change the order of the spectral positions between the transitions 1 s 1 2 p 2 nl 1 − 1 s 2 2 p 1 nl 1 and 1 s 1 2 s 1 2 p 1 nl 1 − 1 s 2 2 s 1 nl 1 . Including or not including the configuration interaction of 1 s 1 2 s 2 nl 1 can result in an energy difference of about 6 eV for the 1 s 1 2 p 2 nl 1 − 1 s 2 2 p 1 nl 1 transitions of Be-like aluminum. This phenomenon reveals the physical reason behind the existence of differences between the experimental transmission and the theoretical transmission for aluminum plasma in the paper by Zhang et al (2009 Phys. Rev. E79 016401 ). For two configurations K i L j M f ... and K i ′ L j ′ M f ′ ..., the strongest configuration interactions may appear when the number of electrons in each shell is the same and the parity for each shell is the same.